In vitro Regeneration of Grass Pea (Lathyrus sativus L.) (Jahangirnagar University Journal of Biological Sciences, 2016)
In vitro regeneration protocol for grass pea (Lathyrus sativus L.) was optimized using different concentrations and combinations of growth regulators. Direct shoot regeneration obtained through shoot organogenesis from different explants of grass pea cultured on MS medium supplemented with Gamborg B5 vitamin containing 6-benzylaminopurine (BAP), Thidiazuron (TDZ) and ?-naphthalene acetic acid (NAA). Highest percentage of shoots were obtained at 4.0 mg/l of BAP on nodal explants. Stunted multiple shoots were developed from nodal explants while 1.5 mg/l TDZ was used. About 56% of direct shoots were also obtained, while the combination of BAP (4.0 mg/l) and NAA (0.5 mg/l) were used. Regenerated plantlets were rooted most effectively (40%) in rooting medium containing half strength of MS basal medium containing 1.0 mg/l NAA. Well rooted plantlets were further successfully acclimatized to ambient humidity level and grown in controlled environment until hardening.Jahangirnagar University J. Biol. Sci. 4(2): 1-8, 2015 (December)